UPAYA PENINGKATAN KOMPETENSI GURU MENYUSUN SILABUS DAN RENCANA PELAKSANAAN PEMBELAJARAN MELALUI BIMBINGAN BERKELANJUTAN DI SDN 002 KUNTU KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR - Enni Betti (Cerdas Proklamator, 2019)
The purpose of the School Action Research (PTS) is to determine the competencies of teachers at SDN 002 Kuntu in developing syllabi and lesson plans and making efforts to improve them. This was done based on the results of observations made by researchers and found some fundamental problems experienced by the teachers. The problems found, namely (1) teachers are less able to tighten the Learning Implementation Plan (RPP) properly; (2) the teacher does not refer to the Syllabus and Implementation Plan in the learning process in the classroom; (3) teachers tend to assume that the old methods and strategies they have implemented have completed many students; (4) the teacher is still fixated to use the Learning Implementation Plan (RPP) that has been designed by the previous teachers. The method implemented is continuous bombardment. Based on the School action research that has been carried out it can be concluded several things, First, Continuous academic supervision is scientifically proven to increase teacher competence in preparing syllabi and lesson plans, namely from 31% to 83% after academic supervision. In addition, the number of good quality lesson plans also increased from 31% to 89%. Second, the steps that lead to an increase in teacher competence in preparing the syllabus and lesson plans include the following steps: (1) announcement of the supervision plan for teachers; (2) conducting individual supervision (3) the principal supervises the class.